Investor Networks in the Stock Market - Ozsoylev, Han N.; Walden, Johan; Yavuz, M. Deniz; Bildik, Recep (Review of Financial Studies, 2014)
We study the trading behavior of investors in an entire stock market. Using an account level dataset of all trades on the Istanbul Stock Exchange in 2005, we identify investors with similar trading behavior as linked in an empirical investor network (EIN). Consistent with the theory of information networks, we find that central investors earn higher returns and trade earlier than peripheral investors with respect to information events. Overall, our results support the view that information diffusion among the investor population influences trading behavior and returns.